Evaluation of drought-tolerant chickpea genotypes (Cicer arietinum L.) using morphophysiological and phytochemical traits - Fazeli-Nasab, Bahman; Vessal, Saeedreza; Bagheri, Abdolreza; Malekzadeh-Shafaroudi, Saeid (Frontiers in Plant Science, 2025)
Chickpea (Cicer arietinum L.), through a series of morphological, physiological, biochemical, and molecular changes, would tolerate abiotic stresses such as water deficiency. Accordingly, two separate experiments were conducted to investigate phytochemical and morphophysiological traits of various candidate chickpea genotypes in response to drought stress. In the first experiment, morphological and phytochemical traits were evaluated by maintaining pots at 70% water holding capacity (WHC) and applying gradual drought stress (to 50% and 25% WHC) to four- to six-week-old seedlings. In the second experiment, the stressed plants were exposed to progressive drought stress for biochemical measurements, while control plants were irrigated at 70% WHC. The highest photosynthetic water use efficiency (9.94 µmolCo2/µmolH2o) under drought stress belonged to the MCC552 genotype, followed by the MCC696 genotype with 7.25. The highest chlorophyll content (SCMR) was recorded in MCC537 (0.99 µg/cm²), followed by MCC352 (0.89 µg/cm²). The deepest root depth (70.83 cm) was observed in MCC537, followed by MCC552 (69.36 cm). Root diameter increase under stress conditions compared to normal conditions only in MCC352 and MCC552. However, leaf area was higher in MCC552 and MCC537 under drought stress conditions. The SCMR(μg/cm²) was highest in the MCC552 (1.48), followed by MCC696(1.32) and MCC80 (1.31). The highest proline level was observed in the MCC552, which increased with drought stress severity. The lowest level of Malondialdehyde was observed in the MCC696 genotypes, while the highest catalase level was found in the MCC696, followed by the MCC537 and MCC552. Based on root depth, root length, diameter, leaf area, as well as phytochemicals traits, especially proline, MCC552 and MCC696 were identified as the most tolerant genotypes to drought stress.